Study of Fly Ash Glass-Ceramic Surface Modification - Ren, Qifang; Ding, Yi; Hu, Puhua; Wang, Lijiu (Asian Journal of Chemistry, 2013)
By ion exchanged to surface of fly ash glass-ceramic in the solution of KNO3 holding for 4 h at 300 ºC, flexure strength is enhanced 17 %. The ion exchange was thoroughly examined by energy spectrum analysis and lots of columnar crystal were found on the surface of glass-ceramic.